2021
DOI: 10.1186/s41479-021-00085-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prophylactic administration of antipyretics on the immune response to pneumococcal conjugate vaccines in children: a systematic review

Abstract: Background Prophylactic administration of antipyretics at the time of immunization seems to decrease some side effects, however reduced immune responses have been reported in some studies. This systematic review aimed to investigate the effect of prophylactic use of antipyretics on the immune response following administration of pneumococcal conjugate vaccines (PCVs). Methods A systematic review of randomized controlled trials and observational stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Neither immediate nor delayed prophylactic ibuprofen use had an impact on the immune responses to primary or booster vaccination in infants receiving the PHiD-CV vaccine 21 . Similarly, children receiving the inactivated influenza vaccine did not generate lower immune responses if they had received prophylactic ibuprofen, compared with those not receiving ibuprofen 20 , 31 .…”
Section: Effect Of Analgesic and Antipyretic Medicines On Immune Resp...mentioning
confidence: 91%
“…Neither immediate nor delayed prophylactic ibuprofen use had an impact on the immune responses to primary or booster vaccination in infants receiving the PHiD-CV vaccine 21 . Similarly, children receiving the inactivated influenza vaccine did not generate lower immune responses if they had received prophylactic ibuprofen, compared with those not receiving ibuprofen 20 , 31 .…”
Section: Effect Of Analgesic and Antipyretic Medicines On Immune Resp...mentioning
confidence: 91%
“… 21 , 68 Although prophylactic paracetamol may decrease the immunogenicity of other vaccines (e.g., PCV7, 10-valent pneumococcal conjugate vaccine, PCV13, and PHiD-CV), it is not known whether this has clinical relevance in real-world clinical practice. 69 , 70 …”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31][32][33] Recently, one systemic review was done for the use of paracetamol at the time of pneumococcal vaccination, which provides evidence for its use without affecting the optimum immune response. 34 One study had also been done to quantify the immune response by hemagglutination-inhibition titers and microneutralization titers post-H1N1 vaccine. They used paracetamol or ibuprofen as an antipyretic or analgesic 2 days before vaccination (pre-vaccination day and vaccination day), and they found that these medicines have no effect on immunogenicity after vaccination.…”
Section: Discussionmentioning
confidence: 99%